Sintesis dan karakterisasi metil selulosa dari kulit biji kakao dengan response surface method - Atia Fizriani; Woro Setiaboma; Djagal Wiseso Marseno; Supriyanto Supriyanto (AGROINTEK, 2024)
The cocoa shell, a by-product of the cacao industry, is a potent source of cellulose, which can be modified into its derivatives in the food industry. One of these derivatives is methylcellulose (MC) that is performed by methylation using dimethyl sulfate. The synthesis process of methylcellulose can affect its characteristics. Food-grade methylcellulose typically had a degree of substitution (DS) ranging from 1.45 to 2.00. This study aimed to determine the optimum conditions for synthesizing food-grade MC and to characterize its properties. The synthesis of MC involved three variables: the concentration of NaOH solution, dimethyl sulfate addition, and methylation temperature. The synthesis of MC was optimized using Response Surface Methodology (RSM) central composite design (CCD) based on its degree of substitution (DS). Several characteristics of the MC were analyzed, including its degree of substitution (DS), oil-holding capacity (OHC), water-holding capacity (WHC), lightness, and crystallinity.The results indicated that the optimal conditions for synthesizing MC were a NaOH concentration of 21.29% (w/v), dimethyl sulfate addition of 3.62 ml, and a temperature of 51.09 C for 180 minutes. The properties of the optimized MC were DS 1.93±0.04, OHC 2.53±0.05 g/g, WHC 3.04±0.10 g/g, lightness 84.32±0.67 g/g, solubility 11.94±1.04% (db), and crystallinity index 40.21%. These research findings provide valuable knowledge about the ideal conditions for synthesizing food-grade MC and offer insights into its properties, thus facilitating its potential applications in the food industry.